Learning Materials and Learning Methods in Materials for Product Course Basic Product Design Education - Ariani Rachman; Awang Eka Novia R; Gihon Nugrahadi (Aliansi Desainer Produk Industri Indonesia (ADPII), 2019)
Materials for Product courses are given in the first and second semesters which are part of basic education in the curriculum of product design courses, Faculty of Art and Design, Trisakti University. After taking the course, students are expected to have a competency to apply the knowledge in choosing and using the right materials in the products to be designed. Although the course leads to engineering materials knowledge, the learning materials and methods remain in the perspective of product design as the designation is for the students of the Product Design Program. This paper aims to discuss the right learning materials and learning methods delivered in Materials for Product to the students of Product Design Programs in order to achieve the goals. The conclusion of the discussion in this paper recommends that problem based-learning method is an appropriate learning method to be applied.